2020
DOI: 10.3390/app10092999
|View full text |Cite
|
Sign up to set email alerts
|

Energy Spectrum Study and Optimal Design of an Inerter-Based Structure Considering the Underlying Soil

Abstract: As a classic inerter system, the tuned viscous mass damper (TVMD) has been proven to be efficient for vibration control. It is characterized by an amplification effect, where the deformation of the dashpot in the TVMD can be larger than that of a single dashpot, providing enhanced energy dissipation. However, the contribution of this system to the enhancement of the energy dissipation quantity and vibration control remains unclear. To deal with this, and considering the underlying soil, this study proposes a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Therefore, a constitutive model based on the classical Davidenkov method was developed and utilized to simulate the dynamic behavior of the surrounding soil. Details and validation of this model can be found elsewhere [34]; briefly, the tangent shear modulus tt G  for initial loading is Figure 4. Model of soil-underground structure interaction system controlled by conventional isolation system (CIS) and by NSAS combined with an isolator.…”
Section: Soil and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a constitutive model based on the classical Davidenkov method was developed and utilized to simulate the dynamic behavior of the surrounding soil. Details and validation of this model can be found elsewhere [34]; briefly, the tangent shear modulus tt G  for initial loading is Figure 4. Model of soil-underground structure interaction system controlled by conventional isolation system (CIS) and by NSAS combined with an isolator.…”
Section: Soil and Boundary Conditionsmentioning
confidence: 99%
“…Therefore, a constitutive model based on the classical Davidenkov method was developed and utilized to simulate the dynamic behavior of the surrounding soil. Details and validation of this model can be found elsewhere [34]; briefly, the tangent shear modulus G t+∆t for initial loading is…”
Section: Soil and Boundary Conditionsmentioning
confidence: 99%
“…Pietrosanti et al 27 optimized an SDOF structure with a TMDI by various methods and analyzed it in comparison with conventional TMD structures, then found that the TMDI has better performance and robustness in reducing the dynamic response. Chen et al 28 optimized inerter-based structure using an energy-based method considering the interaction between the structure and the soil. Pan and Zhang 29 derived the analytical expressions of the stochastic responses of an SDOF structure with the inerter system.…”
Section: Introductionmentioning
confidence: 99%